2000
DOI: 10.1016/s0378-1127(99)00131-0
|View full text |Cite
|
Sign up to set email alerts
|

Songbird response to group selection harvests and clearcuts in a New Hampshire northern hardwood forest

Abstract: Clearcutting creates habitat for many species of early successional songbirds; however, little information is available on bird use of small forest openings created by group selection harvests. Group selection harvests are increasing on the White Mountain National Forest due to negative public response to clearcutting. The objective of this study was to determine if avian species richness and composition differ between clearcut and group selection openings, and between mature stands and the uncut portions of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 27 publications
8
99
0
1
Order By: Relevance
“…In New Hampshire, numbers of Brown Creepers were reduced in partial cuts (Costello et al 2000, King et al 2001). In the northern Appalachian Plateau in Pennsylvania, USA, Brown Creepers were more than twice as abundant in old-growth hemlock-hardwood than in younger forests (Haney andSchaadt 1996, Haney 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In New Hampshire, numbers of Brown Creepers were reduced in partial cuts (Costello et al 2000, King et al 2001). In the northern Appalachian Plateau in Pennsylvania, USA, Brown Creepers were more than twice as abundant in old-growth hemlock-hardwood than in younger forests (Haney andSchaadt 1996, Haney 1999).…”
Section: Discussionmentioning
confidence: 99%
“…We avoided group selection cuts (which are <0.6 ha) 144 because previous studies showed that these primarily support mature-forest and canopy-145 gap specialists rather than shrubland species, and thus are different from larger openings 146 (Costello et al, 2000). Adjacent study sites were separated from one another by at least 147 10 m of forest.…”
Section: Introduction 58 59mentioning
confidence: 99%
“…Studies conducted in much smaller forest openings created by single tree and group selection up to 2 acres generally agree that these areas are not sufficient to satisfy the requirements of the diverse array of early successional shrubland birds (Annand and Thompson 1997, Costello et al 2000, Moorman and Guynn 2001, Robinson and Robinson 1999. In the northeast, some shrubland birds have territory sizes of up to 3 acres, so openings need to be at least this large if the objective is to provide for the range of species within this habitat group (Chandler et.…”
Section: E F Discussion and Management Implicationsmentioning
confidence: 99%